Beyond Dravet Syndrome: Characterization of a Novel, More Severe SCN1A-Linked Epileptic Encephalopathy. Issue 4 (July 2019) - Beck, Veronica C.; Hull, Jacob M.; Isom, Lori L.
Not All SCN1A Epileptic Encephalopathies Are Dravet Syndrome: Early Profound Thr226Met Phenotype Sadleir LG, Mountier EI, Gill D, et al. Neurology . 2017;89(10):1035-1042. Objective: To define a distinct SCN1A developmental and epileptic encephalopathy with early onset, profound impairment, and movement disorder. Methods: A case series of 9 children were identified with a profound developmental and epileptic encephalopathy and SCN1A mutation. Results: We identified 9 children 3 to 12 years of age; 7 were male. Seizure onset was at 6 to 12 weeks with hemiclonic seizures, bilateral tonic-clonic seizures, or spasms. All children had profound developmental impairment and were nonverbal and nonambulatory, and 7 of 9 required a gastrostomy. A hyperkinetic movement disorder occurred in all and was characterized by dystonia and choreoathetosis with prominent oral dyskinesia and onset from 2 to 20 months of age. Eight had a recurrent missense SCN1A mutation, p.Thr226Met. The remaining child had the missense mutation p.Pro1345Ser. The mutation arose de novo in 8 of 9; for the remaining case, the mother was negative and the father was unavailable. Conclusions: Here, we present a phenotype-genotype correlation for SCN1A . We describe a distinct SCN1A phenotype, early infantile SCN1A encephalopathy, which is readily distinguishable from the well-recognized entities of Dravet syndrome and genetic epilepsy with febrile seizures plus. This disorder has an earlier age at onset, profound developmental impairment, and a distinctive hyperkinetic movement disorder, setting it apart from Dravet syndrome. Remarkably, 8 of 9 children had the recurrent missense mutation p.Thr226Met. : SCN1A Gain of Function in Early Infantile Encephalopathy Berecki G, Bryson A, Terhag J, et al. Ann Neurol . 2019; 85:514-525. Objective: To elucidate the biophysical basis underlying the distinct and severe clinical presentation in patients with the recurrent missense SCN1A variant, p.Thr226Met. Patients with this variant show a well-defined genotype–phenotype correlation and present with developmental and early infantile epileptic encephalopathy that is far more severe than typical SCN1A Dravet syndrome. Methods: Whole cell patch clamp and dynamic action potential clamp were used to study T226M Nav 1.1 channels expressed in mammalian cells. Computational modeling was used to explore the neuronal scale mechanisms that account for altered action potential firing. Results: T226M channels exhibited hyperpolarizing shifts of the activation and inactivation curves and enhanced fast inactivation. Dynamic action potential clamp hybrid simulation showed that model neurons containing T226M conductance displayed a left shift in rheobase relative to control. At current stimulation levels that produced repetitive action potential firing in control model neurons, depolarization block and cessation of action potential firing occurred in T226M model neurons. Fully computationally simulated neuron models recapitulated the findings from dynamic action potential clamp and showed that heterozygous T226M models were also more susceptible to depolarization block. Interpretation: From a biophysical perspective, the T226M mutation produces gain of function. Somewhat paradoxically, our data suggest that this gain of function would cause interneurons to more readily develop depolarization block. This "functional dominant negative" interaction would produce a more profound disinhibition than seen with haploinsufficiency that is typical of Dravet syndrome and could readily explain the more severe phenotype of patients with T226M mutation.